Comparison of Repetitive Cardiac Output Measurements at Rest and End-Exercise by Direct Fick Using Pulse Oximetry vs. Blood Gases in Patients With Pulmonary Hypertension - Duknic, Milos; Lichtblau, Mona; Saxer, Stéphanie; Berlier, Charlotte; Schneider, Simon R.; Schwarz, Esther I.; Carta, Arcangelo F.; Furian, Michael; Bloch, Konrad E.; Ulrich, Silvia (Frontiers in Medicine, 2021)
Background Exact and simultaneous measurements of mean pulmonary artery pressure (mPAP) and cardiac output (CO) is crucial to calculate pulmonary vascular resistance (PVR), which is essential to define pulmonary hypertension (PH). Simultaneous measurements of mPAP and CO are not feasible using the direct Fick (DF) method, due to the necessity to sample blood from the catheter-tip. We evaluated a modified DF method, which allows simultaneous measurement of mPAP and CO without needing repetitive blood samples. Methods 24 patients with pulmonary arterial or chronic thromboembolic PH had repetitive measurements of CO at rest and end-exercise during three phases of a crossover trial. CO was assessed by the original DF method using oxygen uptake, measured by a metabolic unit, and arterial and mixed venous oxygen saturations from co-oximetry of respective blood gases served as reference. These CO-measurements were then compared with a modified DF method using pulse oximetry at the catheter- and fingertip. Results The bias among CO measurements by the two DF methods at rest was -0.26 L/min with limits of agreement of ± 1.66 L/min. The percentage error was 28.6%. At end-exercise, the bias between methods was 0.29 L/min with limits of agreement of ± 1.54 L/min and percentage error 16.1%. Conclusion DF using catheter- and fingertip pulse oximetry is a practicable and reliable method for assessing CO in PH-patients. This method has the advantage of allowing simultaneous measurement of PAP and CO, and frequent repetitive measurements such as needed during exercise.